Langkah Strategis Menangkal Hoax: Suatu Pendekatan Kebijakan dan Hukum - Basuki, Udiyo; Setyawan, Hendradi (Universitas Proklamasi 45, 2022)
Along with the pace of globalization and modernization, information and communication technology is developing very rapidly. Communication media has developed from mainstream mass media to social media, all of which are actually to make human life easier. Different motives and interests cause the media to be used for different purposes. Hoax, for example, is a phenomenon of deviant use of media, the tendency of which is to get to a very serious level, namely to divide unity and integrity.So there need to be strategic steps that must be taken to prevent the spread of hoaxes. Through the approach of diversity and citizenship (digital citizenship) it is hoped that it can improve media literacy skills so that they are technology and information literate. So that people are not easily trapped in leading erroneous opinions. A structural approach in the form of political will from the government is also available. Various regulations in the form of laws and regulations and supporting infrastructure such as the National Cyber and Crypto Agency (BSSN) have also been formed. Thus the handling of various negative content has a strong policy and juridical footing.